2013
DOI: 10.1371/journal.pone.0074548
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Development of a Novel Class of CXCR4 Antagonist Impairing Solid Tumors Growth and Metastases

Abstract: The CXCR4/CXCL12 axis plays a role in cancer metastases, stem cell mobilization and chemosensitization. Proof of concept for efficient CXCR4 inhibition has been demonstrated in stem cell mobilization prior to autologous transplantation in hematological malignancies. Nevertheless CXCR4 inhibitors suitable for prolonged use as required for anticancer therapy are not available. To develop new CXCR4 antagonists a rational, ligand-based approach was taken, distinct from the more commonly used development strategy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(110 citation statements)
references
References 44 publications
(53 reference statements)
4
106
0
Order By: Relevance
“…Similarly, the aggressiveness of a glioblastoma seems to correlate with its CXCR4 expression pattern (25), and a high accumulation of CXCR4 has been reported to be especially prevalent in breast carcinomas of high metastatic potential (5,6). In melanoma and NSCLC, the detection of high CXCR4 expression has even led to the preclinical development of antagonists, with promising results (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the aggressiveness of a glioblastoma seems to correlate with its CXCR4 expression pattern (25), and a high accumulation of CXCR4 has been reported to be especially prevalent in breast carcinomas of high metastatic potential (5,6). In melanoma and NSCLC, the detection of high CXCR4 expression has even led to the preclinical development of antagonists, with promising results (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have recently reported a new family of CXCR4 antagonists developed through a ligand-based approach (45,46). A three-residue segment identified in CXCL12 that was similar to, but in reverse order, to a peculiar inhibitory chemokine secreted by herpes virus 8 (HHV8) vMIP-II was the starting point (59,60).…”
Section: Cxcr4 Antagonists In Developmentmentioning
confidence: 99%
“…The motif Ar1-Ar2-R, where Ar is an aromatic residue, constitutes the core of a cyclic peptide library evaluated for anti-CXCR4 activity. Three peptides (R, S, and I) identified as potent CXCR4 antagonists were demonstrated to reduce the development of metastases in in vivo models (45,46). Recent studies also demonstrated that peptides R, S, and I efficiently mobilize LY6G þ cells better and longer than AMD3100 and increase bone marrow cellularity, mainly of immature precursors, indicating an active hematopoietic stimulation.…”
Section: Cxcr4 Antagonists In Developmentmentioning
confidence: 99%
“…48 Albeit limited by the sample size, the present study demonstrated that high CXCR4 and Mut-KRAS identifies the worst prognostic group within a homogeneous cohort of mCRC with resectable liver metastases undergone to common neoadjuvant therapy. We speculate that the new class of CXCR4 antagonists recently developed 49 may be highly effective in Mut-KRAS CRLMs targeting CXCR4-positive cancer cells and improving T cell access by reducing tolerogenic effect and improving immune response in CRLM patients. ) 46-h continuous infusion; bevacizumab was administered at 5 mg/kg by i.v.…”
Section: Discussionmentioning
confidence: 98%